UDP Pervasive Protocol Design and Implementation on Multi Devices using MyRIO - Mochammad Hannats Hanafi Ichsan; Rizal Maulana; Octavian Metta Wisnu Wardhana (Universitas Ahmad Dahlan, 2022)
Pervasive Computing is one of the practical computing applications to facilitate computer operations by minimizing human interaction with computers. Pervasive Computing has been developed using UDP protocol to recognize the other devices without manual configuration. NI MyRIO device is one of the most reliable devices for the prototyping process. However, there are still not many implementations of data transmission using specific protocols. And the direction of use for smart homes or smart environments is still not widely done. This research contribution implemented Pervasive UDP protocols on PC devices and two NI MyRIO using LabVIEW programming language. UDP protocols are used because they do not require a handshake to recognize another device to reduce delays and have smaller data sizes due to the absence of recognition fields and sequence fields. Each device uses a dual-state machine system design that has a function to detect other devices automatically and act as an application to use the address of another device. PC represents the host, and MyRIO represents the client. Using the same state machine to detect all devices can recognize more than one device on the same network. The obtained test results show that all functional testing scenarios succeeded 100%. The discovery time is averaged at 0.202754 seconds for First MyRIO as First Client and 0.303201 seconds for Second MyRIO as Second Client. The delay in sending data from the host to the client is no more than 2 seconds. Based on this research, MyRIO has the ability to pervasive Computing with other devices. And can be used for prototyping models with good capabilities.